Including the Most Excluded? A Qualitative Study on the Address Registration for People Experiencing Homelessness in Belgium. Issue 6 (July 2023) - Robben, Laure-lise; Roets, Griet; Wagener, Martin; Van Lancker, Wim; Hermans, Koen
In many European countries, one needs a permanent address to be entitled to social rights. To address this minimum prerequisite, mechanisms for administrative inclusion are in place for persons experiencing homelessness, such as the reference address in Belgium. This paper disentangles the non-take-up mechanisms behind this reference address by drawing on interviews with professionals. Our evidence suggests this is a minimum minimorum of social protection, albeit it can reflect and reinforce exclusion of the beneficiaries. This article contributes to the debate on the entitlement and non-take-up of rights, and the possibility of an administrative address that includes the most excluded.